-(9m-10)=-9m-10

Simple and best practice solution for -(9m-10)=-9m-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(9m-10)=-9m-10 equation:


Simplifying
-1(9m + -10) = -9m + -10

Reorder the terms:
-1(-10 + 9m) = -9m + -10
(-10 * -1 + 9m * -1) = -9m + -10
(10 + -9m) = -9m + -10

Reorder the terms:
10 + -9m = -10 + -9m

Add '9m' to each side of the equation.
10 + -9m + 9m = -10 + -9m + 9m

Combine like terms: -9m + 9m = 0
10 + 0 = -10 + -9m + 9m
10 = -10 + -9m + 9m

Combine like terms: -9m + 9m = 0
10 = -10 + 0
10 = -10

Solving
10 = -10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x+75+125+x=180 | | -4(8)-(-5)= | | 4a+37=5a+5(1+3a) | | 4x+50=650 | | 13x-3+2x=4(6x-3)+6 | | 4x-7=5x-3 | | 13-9x=112 | | G/12=-12 | | 10/x=15/24 | | 9m+15=3(5+3m) | | -5x-3+x=15 | | 6(b-1)=-150 | | (-5)4(-1)= | | X/10.5=2.5 | | R+39.3=16.4 | | -72=4n+8 | | -6/2(6x-20y) | | X+y=-56 | | -2(x+9)=-32 | | 3z^2+33=180 | | 5*35+10y=625 | | 15x^2+2x-6=0 | | -2x-4+6x=0 | | 5*40+10y=625 | | 3y=-x(18)+1 | | 15=2(q+4)+2 | | 5+6y=9y+2+(1-y) | | 6f-11=-7 | | 5x=22+6y | | -5-2x=-49 | | 12(x-100)=1800 | | 0=-60x+4 |

Equations solver categories